Homeschooling - Jublina Anthoneta (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
This paper attempts to show that true education does not happen only in a formal school andeducation system. Adequate education for children can be provided in a family or in thehome. School in gerenal is an institution founded on modern values held by modern people.